How the word is passed : a reckoning with the history of slavery across America - Smith, Clint (New York : Little, Brown and Company, 2021)
"'How the Word is Passed' is Clint Smith's revealing, contemporary portrait of America as a slave-owning nation. Beginning in his own hometown of New Orleans, Smith leads the reader through an unforgettable tour of monuments and landmarks - those that are honest about the past and those that are not - that offer an intergenerational story of how slavery has been central in shaping our nation's collective history, and ourselves."--
"The whole city is a memorial to slavery:" Prologue -- "There's a difference between history and nostalgia:" Monticello Plantation -- "An open book, up under the sky:" The Whitney Plantation -- "I can't change what happened here:" Angola Prison -- "I don't know if it's true or not, but I like it:" Blandford Cemetery -- "Our Independence Day:" Galveston Island -- "We were the good guys, right?" New York City -- "One slave is too much:" Gorée Island -- "I lived it:" Epilogue -- About this project.
Includes bibliographical references (pages 299-320) and index.
Keywords: Smith, Clint -- Travel -- Southern States; Slavery -- United States -- History; Slaveholders -- United States -- History; African Americans -- Social conditions -- History; Historic sites -- Southern States; Plantations -- Southern States -- History; Southern States -- Race relations -- History; Southern States -- History, Local